2021
DOI: 10.3389/fcimb.2021.785169
|View full text |Cite
|
Sign up to set email alerts
|

HPV16-LINC00393 Integration Alters Local 3D Genome Architecture in Cervical Cancer Cells

Abstract: High-risk human papillomavirus (hrHPV) infection and integration were considered as essential onset factors for the development of cervical cancer. However, the mechanism on how hrHPV integration influences the host genome structure remains not fully understood. In this study, we performed in situ high-throughput chromosome conformation capture (Hi-C) sequencing, chromatin immunoprecipitation and sequencing (ChIP-seq), and RNA-sequencing (RNA-seq) in two cervical cells, 1) NHEK normal human epidermal keratinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 58 publications
(72 reference statements)
2
26
0
1
Order By: Relevance
“…The HBV, EBV, HPV, and HTLV-1 genomes contain binding sites for the transcriptional repressor and chromatin regulator CCCTC-binding factor (CTCF) [26,[73][74][75], which mediates the formation of loops in the human genome and establishes boundaries between hetero-and euchromatin [76]. Chromosome conformation capture (Hi-C) studies on human cervical cancer biopsies harboring HPV integrations into the RIG CCDC106, as well as HPV provirusharboring cell lines, showed changes within host genomic topologically associating domains (TADs) as well as altered TAD borders in the vicinity of the integration site [25,77,78]. Changes in nuclear architecture were associated with the formation of new virus-host DNA interactions, including with host enhancer sequences [25,78].…”
Section: Box 1 Chromatin Remodeling Resulting From Viral Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBV, EBV, HPV, and HTLV-1 genomes contain binding sites for the transcriptional repressor and chromatin regulator CCCTC-binding factor (CTCF) [26,[73][74][75], which mediates the formation of loops in the human genome and establishes boundaries between hetero-and euchromatin [76]. Chromosome conformation capture (Hi-C) studies on human cervical cancer biopsies harboring HPV integrations into the RIG CCDC106, as well as HPV provirusharboring cell lines, showed changes within host genomic topologically associating domains (TADs) as well as altered TAD borders in the vicinity of the integration site [25,77,78]. Changes in nuclear architecture were associated with the formation of new virus-host DNA interactions, including with host enhancer sequences [25,78].…”
Section: Box 1 Chromatin Remodeling Resulting From Viral Integrationmentioning
confidence: 99%
“…Changes in nuclear architecture were associated with the formation of new virus-host DNA interactions, including with host enhancer sequences [25,78]. Associated changes in gene expression included the transcriptional down-and upregulation of genes encoding tumor-suppressor (PEG3 and KLF12) and proto-oncogene (CCDC106) functions in HPV-harboring cell lines and cervical cancer biopsies [77][78][79]. Similarly, assays revealed that HBV, upon integration, establishes 3D contact regions with cellular chromatin [80,81].…”
Section: Box 1 Chromatin Remodeling Resulting From Viral Integrationmentioning
confidence: 99%
“…This may be due to the fact that the host chromatin structure is influencing the HPV associated genomic alterations (amplification/translocation) during the integration processes or limiting the HPV integration mediated chromatin interaction changes to intra-TAD because of the insulation property of TAD boundaries. Recent studies have shown that HPV integration can cause changes in the local TAD structures in advanced cervical cancers (Cao et al 2020) and also in human cell lines: HPV16 integration in W12 (prior to clonal selection) (Groves et al 2021) and HPV16 integration in SiHA cell line (Xu et al 2021). Our results further extend this observation genome-wide in cervical tumours and show that the majority of the HPV integration induced chromatin changes and associated gene expression changes are mostly confined to the same TAD.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported that integration may occur in different chromosomes and regions of the human genome. Furthermore, vector integration preferentially occurs at fragile sites, transcriptionally active regions and those recurrently involved in translocation events [19][20][21][22][23]. However, most of these studies have been limited to human immunodeficiency virus (HIV), human papillomavirus (HPV) or Murine leukemia virus (MLV) infected cells and little is known about the characteristics of viral integration events in CAR T-cells.…”
Section: Introductionmentioning
confidence: 99%